Censorship: Unspecified social media services (India) - Voidly (Voidly Global Censorship Index, 2024)
WARNING severity censorship detected in India. Data sourced from CensoredPlanet.
Censorship Incident ID: IN-2024-0003. Severity: warning. Confidence: 75%